EVALUATION OF LEARNING OUTCOMES ON SOCIAL ARITHMETIC MATERIAL BY APPLYING THE STUDENT TEAM ACHIEVEMENT DIVISION (STAD) COOPERATIVE LEARNING MODEL - Siti Mawaddah (Prodi Tadris Matematika Universitas Muhammadiyah Aceh, 2024)
The aim of this research is to determine the evaluation of learning outcomes in social arithmetic material by applying the student team achievement division (STAD) cooperative learning model. The population in this research is all class VII students at MTsS Baitul Arqam Sibreh Aceh Besar, the sample for this research is secondary school MTsS Baitul Arqam Sibreh. The results of student learning tests using the STAD type cooperative learning model also show that 100% of students have completed their studies, meaning that all 25 students in class VII have completed their studies. The completeness of the learning outcomes shows that students' mastery of understanding of social arithmetic material is very good.